139k views
1 vote
confirm that F and g are inverses by showing that f(g(x))=x and g(f(x))=x f(x)=x^3+4 and g(x)=3(sqrt of x-4)

User Apdm
by
5.9k points

1 Answer

3 votes

we are given


f(x)=x^3+4


g(x)=\sqrt[3]{x-4}

Calculation of f(g(x)):


f(x)=x^3+4

replace x = g(x)


f(g(x))=(g(x))^3+4

we can plug g(x)


f(g(x))=(\sqrt[3]{x-4})^3+4


f(g(x))=x-4+4


f(g(x))=x

Calculation of g(f(x)):

we are given


g(x)=\sqrt[3]{x-4}

replace x =f(x)


g(f(x))=\sqrt[3]{f(x)-4}

we can replace f(x)

we get


g(f(x))=\sqrt[3]{x^3+4-4}


g(f(x))=\sqrt[3]{x^3}


g(f(x))=x

we can see that


f(g(x))=g(f(x))=x

so, f(x) and g(x) are inverse of each other..........Answer

User Thomas Koch
by
6.0k points